Open source, low cost combine harvester - Sazim, Md. Abdullah Bin; Nain, S.M. Zulkar; Hassan, Akibul (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.